How frequent is routine use of probiotics in UK Neonatal Units? - Patel,N; NeoTRIPs,CG; Evans,K; Berrington,J; Szatkowski,L; Costeloe,K; Ojha,S; Fleming,P; Battersby,C (BMJ Paediatrics Open, 2023)
Objective: There is a lack of UK guidance regarding routine use of probiotics in preterm infants to prevent necrotising enterocolitis, late-onset sepsis, and death. As practices can vary, we aimed to determine the current usage of probiotics within neonatal units in the United Kingdom.Design and setting: Using NeoTRIPS, a trainee-led neonatal research network, an online survey was disseminated to neonatal units of all service levels within England, Scotland, Northern Ireland, and Wales in 2022. Trainees were requested to complete one survey per unit regarding routine probiotic administration. Results: 161/188 (86%) neonatal units responded to the survey. 70/161 (44%) respondents routinely give probiotics to preterm infants. 45/70 (64%) use the probiotic product Lactobacillus acidophilus NCFM/Bifidobacterium bifidum Bb-06/Bifidobacterium infantis Bi-26 (Labinic™). 57/70 (81%) start probiotics in infants ≤32 weeks gestation. 33/70 (47%) had microbiology departments that were aware of the use of probiotics and 64/70 (91%) had a guideline available. Commencing enteral feeds was a prerequisite to starting probiotics in 62/70 (89%) units. The majority would stop probiotics if enteral feeds were withheld (59/70; 84%) or if the infant was being treated for necrotising enterocolitis (69/70; 99%). 24/91 (26%) units that did not use probiotics at the time of the survey were planning to introduce them within the next 12 months. Conclusion: More than 40% of all UK neonatal units that responded are now routinely administering probiotics, with variability in the product used. With increased probiotic usage in recent years, there is a need to establish whether this translates to improved clinical outcomes.